The effectiveness of giving lemon aromatherapy to reduce the frequency of emesis gravidarum in pregnant women - Idawati; Novita, Widiya; Pusvita, Henny; Susanti, Heri; Intan, Meurah (Trigin Institute, 2023)
Background: Emesis gravidarum is astate of nausea sometimes accompanied by vomiting that occurs in early pregnancy. These symptoms usually occur 6 weeks after the first day of the last menstrual period and last approximately 10 weeks, but in some cases can continue until the second and third trimester of pregnancy. About 50-90% of pregnant women experience complaints of nausea and vomiting. This complaint is usually accompanied by hypersalivation (excessive salivation), headaches, flatulence, and weakness in the body. These complaints are commonly known as